Formation et ressources praxéologiques de l’enseignant débutant en danse - Alexandra Arnaud-Bestieu (Recherches en Éducation)
This article attempts to report the link between a teachers’ training and processes of construction of a contemporary dance reference at primary school. This research is based on observation of a short teachers’ training (3 hours) dispensed in their institution and the observation during the teaching unit proposed by one of the participants, novice in this discipline. This research – in situ data collection – is conducted through two theories, the Joint Action Theory in Didactics (Sensevy et Mercier, 2007; Schubauer-Leoni et Leutenegger, 2008) and the Anthropological Theory of Didactics (Chevallard, 1989,1999). This theorectical position brings into light relations between knowledge coconstruction phenomena during the class and subject-specific competences of the teacher. The analysis of this clinical case brings into light incidence of physical practice on constitution of disciplinary epistemologie mobilized by the teacher so as the difficulties of teaching dance.